Medication-related osteonecrosis of the jaw in oncological patients with skeletal metastases: conservative treatment is effective up to stage 2. Issue 8 (October 2017) - Coropciuc, R.G.; Grisar, K.; Aerden, T.; Schol, M.; Schoenaers, J.; Politis, C.
Abstract: There is currently no widespread strategy for treating medication-related osteonecrosis of the jaw (MRONJ), so our aim was to evaluate retrospectively the outcome of a minimally invasive treatment protocol for patients with both MRONJ and cancer. We designed a retrospective cohort study of patients with cancer who had been diagnosed with MRONJ after treatment with denosumab or bisphosphonates given intravenously. Primary outcome measures were improvement in the clinical stage of MRONJ and the time course to its resolution. Secondary outcome measures included the incidence of risk factors and patterns of treatment. Seventy-nine patients with 109 lesions were enrolled, and their characteristics, presentation of the lesions, complications, and relations to previous oral interventions were recorded. Treatment depended on the stage of disease, and included conservative medical, and minimally-invasive surgical, procedures. There was complete healing and resolution of disease in 38/57 stage 1 lesions, 30/47 stage 2 lesions, and 3/5 stage 3 lesions. The symptoms improved in 16/47 stage 2 lesions, and 2/5 stage 3 lesions. Fifteen of the stage 1 lesions, and one of the stage 2 lesions, failed to respond. Despite the possibility of an aggressive approach to the treatment of MRONJ, conservative treatment remains the first line of defence as regression is obvious, with evidence of no evolution to a higher stage. In our experience surgical intervention is recommended in persistent stage 3 MRONJ that has failed to respond to conservative treatment.